Phase stabilization of a coherent fiber network by single-photon counting - Yanikgonul, Salih (2022)
Coherent optical fiber networks are extremely sensitive to thermal, mechanical, and acoustic noise, which requires elaborate schemes of phase stabilization with dedicated auxiliary lasers, multiplexers, and photodetectors. This is particularly demanding in quantum networks operating at the single-photon level. Here, we propose a simple method of phase stabilization based on single-photon counting and apply it to quantum fiber networks implementing single-photon interference on a lossless beamsplitter and coherent perfect absorption on a metamaterial absorber. As a proof of principle, we show dissipative single-photon switching with visibility close to 80%. This method can be employed in quantum networks of greater complexity without classical stabilization rigs, potentially increasing efficiency of the quantum channels.